Earnings Management under Political Crisis in Thailand - Jevasuwan, Supavinee; Wongsorntham, Ausa (Journal of Humanities and Social Sciences Thonburi University, 2024)
This research aims to study the relationship between political crisis and earnings management of companies listed on the Stock Exchange of Thailand. The political crisis in this context refer to the two coup events that occurred in Thailand. The sample group of this research consists of companies listed on the stock exchanges of four countries: Thailand, Indonesia, South Korea and the Philippines. This research uses the method differences-in-difference to test the differences between two samples groups: the treatment group and the control group, before and after the political crisis. The research findings indicate that the impact of crisis leading to political crisis, such as the coup in Thailand, prompted executives to engage in earnings management in order to achieve their predefined objectives. Additionally, the study found that the severity of political crisis is correlated with the level of earnings manipulation. Specifically, when the political crisis is more severe, company executives are more likely to engage in earnings manipulation, whereas when the crisis is less severe, the likelihood of such behavior decreases.